Multi-stakeholder identification and prioritization of human–tiger conflict reduction measures in Chitwan National Park, Nepal - Rajendra Dhungana; Tek Maraseni; Benjamin L. Allen; Ram Chandra Kandel; Pashupati Nath Koirala; Ganesh Pant; Rishi Ranabhat (Oryx)
The identification and implementation of conflict reduction measures are necessary to reduce predator attacks on people and livestock and to minimize human encroachment into predator habitats. We identified potential human–tiger conflict reduction measures and prioritized these measures for Chitwan National Park, Nepal. We identified these measures through a literature review, key informant interviews and a local stakeholder workshop. We prioritized the identified measures using a questionnaire survey of victims of tiger attacks (farmers, forest users and fishers), beneficiaries of tiger conservation (tourist guides, Jeep and elephant safari operators, tour and hotel operators and business operators) and National Park managers. We identified 22 measures (12 preventative, five reactive and five mitigative) as having potential for reducing negative interactions between people and tigers. Amongst these, we identified compensation payments, tiger-proof fences and habitat and prey management as high-priority measures. Conflict reduction priorities also varied amongst stakeholder groups. The victims assigned the highest priority to the construction of tiger-proof fences, whereas beneficiaries identified the management of habitat and prey as their highest priority. Compensation payments were the first preference of National Park managers and were amongst the top two priorities of all stakeholder groups. We recommend the adoption of the identified stakeholder priorities for reducing human–tiger conflict around Chitwan National Park and encourage consideration of the variations in priorities between stakeholder groups during policy development and decision-making.